1995
DOI: 10.1073/pnas.92.17.7734
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic development: paradoxical relation between impaired cell growth at low population density and excessive growth at high density.

Abstract: The role of heritable, population-wide cell damage in neoplastic development was studied in the 28 L subline of NIH 3T3 cells. These cells differ from the 173c subline used previously for such studies in their lower frequency of "spontaneous" transformation at high population density and their greater capacity to produce large, dense transformed foci. Three cultures of the 28 L subline of NIH 3T3 cells were held under the constraint ofconfluence for 5 wk (5 wk 10 assay) and then assayed twice in succession (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Our data also suggest that SSeCKS ensures contact-inhibited growth through a secondary, fail-safe function, that being an ability to scaffold residual cyclin D protein in the cytoplasm. In agreement with this, several studies have shown that continuous plating of untransformed chick embryo fibroblasts at high densities increases the frequencies of spontaneous oncogenic transformation compared to cells plated at low densities (13,14,50).…”
Section: Discussionmentioning
confidence: 49%
“…Our data also suggest that SSeCKS ensures contact-inhibited growth through a secondary, fail-safe function, that being an ability to scaffold residual cyclin D protein in the cytoplasm. In agreement with this, several studies have shown that continuous plating of untransformed chick embryo fibroblasts at high densities increases the frequencies of spontaneous oncogenic transformation compared to cells plated at low densities (13,14,50).…”
Section: Discussionmentioning
confidence: 49%
“…We have noted previously that transformed cells multiply more slowly at low population density in 10% CS than their nontransformed counterparts (33,34). We have noted previously that transformed cells multiply more slowly at low population density in 10% CS than their nontransformed counterparts (33,34).…”
Section: Resultsmentioning
confidence: 81%
“…The impairment of growth, most apparent at low density, is a common accompaniment of transformation and apparently reflects genetic damage to the cells (3)(4)(5)31,33,34,37). By contrast, the transformed cells multiplied at the same rate as they did at low population density, although exhibiting a shorter lag period.…”
Section: Resultsmentioning
confidence: 99%
“…It would be of particular interest to determine whether the expression of these genes is altered by radically different environmental conditions such as would be encountered in cells of the colonic epithelium. Such a situation might provide an explanation for the observed variations in transformation efficiency of cells in culture when subjected to varying conditions of cell density and serum concentration (Rubin et al, 1992(Rubin et al, , 1995, as well as the effects described here.…”
mentioning
confidence: 64%